China’s choice on the participation in establishing marine protected areas in areas beyond national jurisdiction - Yu, Minyou; Huang, Yuwen (Frontiers in Marine Science, 2023)
Marine biodiversity is facing grave threats, particularly in areas beyond national jurisdiction (ABNJ), where sustainable management and effective implementation of governance is lacking yet. The establishment of marine protected areas in areas beyond national jurisdiction is one of the debated issues during the negotiations of BBNJ Agreement and it is considered to be a feasible conservation tool. There has been both positive and negative impact on China when choosing whether or not to participate in the establishment of marine protected areas in ABNJ. It is concluded that China should actively participate in international negotiations and seriously assessing the impacts of establishing these protected areas before making its own decision in order to strike a balance between the conservation and utilization of marine resources.